Radiological features of azygos and hemiazygos continuation of inferior vena cava: A case report. Issue 17 (April 2018) - Liu, Yin; Guo, Dan; Li, Jie; Zhang, Xuebin; He, Jian; Huang, Mei; Dai, Jinghong; Cai, Hourong
Abstract: Rationale: Azygos and hemiazygos continuation of the inferior vena cava (IVC) is uncommon. It is rare especially when it is not associated with congenital heart disease or deep venous thrombosis. Patient concerns: We report an interesting case of an interstitial lung disease with an interrupted IVC with azygous and hemiazygos continuation. A 67-year-old man suffered from cough and shortness of breath. Diagnoses: Computed tomography revealed absence of the hepatic segment of the IVC with azygos and hemiazygos continuation. The patient did not have congenital anomalies of the remaining thoracoabdominal vasculature and viscera. The diagnosis of azygos and hemiazygos continuation of IVC was made by inferior venacavography. Interventions: There was no significant association between interstitial lung disease and expanded azygos and hemiazygos veins. The patient was treated with corticosteroids. Outcomes: After 6 months of follow-up, the patient was asymptomatic. Lessons: It is important to recognize the enlarged azygos vein at the confluence with the superior vena cava and in the retrocrural space to avoid misdiagnosis as a right-sided paratracheal mass or retrocrural adenopathy.